1996
DOI: 10.1051/jp3:1996173
|View full text |Cite
|
Sign up to set email alerts
|

Three-Layered Photovoltaic Cell with an Enlarged Photoactive Region of Codeposited Dyes

Abstract: Three-layered organic solar cells with an interlayer of codeposited dyes of ptype Copper Phthalocyanine (CuPc) and n-type 5,10,15,20-Tetra (4-Pyridil)21H,23H-Porphine (TPyP) between the respective dye layers were prepared and characterised. The analysis of their dark la lumibre avec une longueur d'onde de 520 nm et une intensit4 lumineuse de 30 ~IW cm~1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“… reflects the current losses from the pinholes and traps in the film. Established relationships describing J-V behavior in OSCs and directly accounting for resistance effects on cell performance are the following [ 61 , 62 , 63 , 64 ]: where, is the diode current density, is the leakage current density, is the photogenerated current density, is the reverse saturation current, e is the elementary charge, n is the diode ideality factor, k B is Boltzmann’s constant, and T is temperature. is an undesirable current injected from the electrodes in the opposite direction to .…”
Section: Structure and Characterization Of Organic Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“… reflects the current losses from the pinholes and traps in the film. Established relationships describing J-V behavior in OSCs and directly accounting for resistance effects on cell performance are the following [ 61 , 62 , 63 , 64 ]: where, is the diode current density, is the leakage current density, is the photogenerated current density, is the reverse saturation current, e is the elementary charge, n is the diode ideality factor, k B is Boltzmann’s constant, and T is temperature. is an undesirable current injected from the electrodes in the opposite direction to .…”
Section: Structure and Characterization Of Organic Solar Cellsmentioning
confidence: 99%
“…R sh reflects the current losses from the pinholes and traps in the film. Established relationships describing J-V behavior in OSCs and directly accounting for resistance effects on cell performance are the following [61][62][63][64]:…”
Section: Structure and Characterization Of Organic Solar Cellsmentioning
confidence: 99%
“…In this context, the observed asymmetry of the dark I-V characteristics is due to the heterojunction present at the ZnSe/ZnTe interface, the Au back-electrode and the ZnO/ITO top-electrode featuring a good ohmic behaviour. Analysing further the measured I-V characteristics in the dark, we found that it follows the modified Shockley-Read equation [47][48][49][50]:…”
Section: Electrical and Photoelectrical Measurementsmentioning
confidence: 84%
“…where I is the current flowing just through the heterojunction, I 0 is the saturation current, q is the elementary charge, U is the applied voltage to the whole structure, n is the ideality factor of the diode, k B is the Boltzmann constant, and R S and R Sh are the series and shunt resistances, respectively. By performing the logarithmic plot of the intensity of the current, i.e., Equation ( 5) at forward bias, as a function of the applied voltage, i.e., ln I versus U (see Figure 5b), a first determination of the diode ideality factor is obtained (n 1 = 5.44) along with the saturation current (I 0 1 = 6.93 × 10 −9 A) [26,49,50]. Both values are not accurately computed due to the great impact of series and shunt resistances, i.e., R S and R Sh , on the linearity of this plot.…”
Section: Electrical and Photoelectrical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation